Buschke-Löwenstein Tumor: About an Observation and Review of Literature (Archives of Clinical and Medical Case Reports, 2021)
Buschke - Löwenstein tumor is an uncommon disease associated with human papillomavirus infection. It occurs most often in pubescent male subjects with sexual activity. It is located at the level of the external genitalia. The diagnosis is based on the histological study and the treatment is essentially surgical with complete and wide excision in order to avoid recurrence. The prevention of this tumor is based on the treatment of condylomata acuminata as a sexually transmitted disease.